Online Peer Support Programs for Young People with a Parent Who has a Mental Illness: Service Providers' Perspectives. Issue 3 (3rd July 2019) - Price-Robertson, Rhys; Reupert, Andrea; Maybery, Darryl
ABSTRACT: Young people with a parent or parents who have mental illness are at a higher-than-average risk of experiencing emotional and behavioural difficulties. Notwithstanding the difficulties experienced by these young people, opportunities to interact with and obtain support from peers living in similar families can be beneficial. While young people face several barriers to participating in face-to-face peer support programs, online approaches potentially provide a different way of obtaining peer support. This paper aims to explore service providers' perspectives on current Victorian peer support programs, as well as the strengths and weaknesses of online approaches to peer support. Semistructured interviews were conducted with 17 mental health professionals who work with families affected by parental mental illness. Participants recognised that many young people miss out on face-to-face peer support programs, and were highly supportive of the idea of online programs. This study suggests that online peer support programs for young people could occupy an important position in the evolving suite of services for Australian families affected by mental illness. IMPLICATIONS: Online approaches to peer support should be included among services for Australian families affected by mental illness. Social workers are well-placed to develop online programs that address the mental health needs of families and young people.